Gilead Sciences and Sovaldi : the cost of a cure (A) - Budish, Benjamin; Lane, Chase; Zaleski, Richard; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Gilead Sciences hepatitis C drug, Sovaldi, proved more effective than the competition and was priced in line with market conditions. However, extremely high cost and large patient population captured the attention of the media, the public, NGOs, and even the government. The controversy deepened when the company revealed the cost in developing countries would be roughly 1% of the cost in the U.S.
Originally published in Budish, B., Lane, C., Zaleski, R., & ORourke, J. S. (2014). Gilead Sciences and Sovaldi: The cost of a cure (A). 14-10 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gilead Sciences (Firm); Business ethics; Strategic planning; Pharmaceutical industry